An Analysis of Speech Errors Made by Students at SMA Negeri 8 Makassar - Andi Nita Putri Sari; Ahmad Talib; Syarifah Faradiba (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aimed to know the types of speech errors made by students and the causes of speech errors. This research uses descriptive research with a qualitative approach and uses observation and interview instruments. The subjects in this study were students of class XI IPA 1 SMA Negeri 8 Makassar in the odd semester of the 2022/2023 academic year. Subjects were selected using the technique of purposive sampling to know the types of students' speech errors and the causes of the student’s speech errors. This research instrument is in the form of an observation and an interview. From the results of the data analysis, the researcher found several kinds of speech errors made by students when speaking and the causes of speech errors made by the students.